2021
DOI: 10.3390/ijms22136877
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Pipeline for Pollen- and Anther-Specific Gene Discovery Based on Transcriptome Profiling Analysis of Maize Tissues

Abstract: Recently, crop breeders have widely adopted a new biotechnology-based process, termed Seed Production Technology (SPT), to produce hybrid varieties. The SPT does not produce nuclear male-sterile lines, and instead utilizes transgenic SPT maintainer lines to pollinate male-sterile plants for propagation of nuclear-recessive male-sterile lines. A late-stage pollen-specific promoter is an essential component of the pollen-inactivating cassette used by the SPT maintainers. While a number of plant pollen-specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…In order to evaluate the transcript abundance in each of the sequenced tissues, we chose genes whose TPM (transcripts per kilobase of exon model per million mapped reads) value was higher than 1.00 as expressed genes (EGs), and we divided the EG into four groups: low expressed genes (LEGs, 1–10 TPM), medium expressed genes (MEGs, 10–30 TPM), high expressed genes (HEGs, 30–300 TPM), and very high expressed genes (VHEGs, ≥300 TPM) [ 39 , 40 ]. Of the 70,199 genes reported or predicted in the Gossypium cotton TM-1 reference genome, we found that pollen grains only have 12,005 EGs occupying 17.1% of known cotton genes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to evaluate the transcript abundance in each of the sequenced tissues, we chose genes whose TPM (transcripts per kilobase of exon model per million mapped reads) value was higher than 1.00 as expressed genes (EGs), and we divided the EG into four groups: low expressed genes (LEGs, 1–10 TPM), medium expressed genes (MEGs, 10–30 TPM), high expressed genes (HEGs, 30–300 TPM), and very high expressed genes (VHEGs, ≥300 TPM) [ 39 , 40 ]. Of the 70,199 genes reported or predicted in the Gossypium cotton TM-1 reference genome, we found that pollen grains only have 12,005 EGs occupying 17.1% of known cotton genes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pollen-specific genes were termed preferentially expressed in pollen or not expressed in other tissues except pollen. Thus, the criterion was used for screened PSGs as reported: (1) a TPM of at least 1 in mature pollen, and (2) expression at least 100-fold higher in pollen than in other vegetative or reproductive tissues [ 40 ]. In total, 1111 PSGs were identified ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations